2016
DOI: 10.1002/aqc.2633
|View full text |Cite
|
Sign up to set email alerts
|

Population crash in Lesotho's endemic Maloti minnow Pseudobarbus quathlambae following invasion by translocated smallmouth yellowfish Labeobarbus aeneus

Abstract: 3. The objectives of the present study were to: (1) establish whether any additional non-native fish species were present in the Mohale catchment; (2) ascertain whether L. aeneus has dispersed into the rivers flowing into Mohale Reservoir; and (3) gauge whether the Mohale population of P. quathlambae is in decline. Twenty-eight sites situated on major rivers flowing into the reservoir, and four sites in the reservoir itself, were surveyed to evaluate changes in fish populations and habitat quality.4. Results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The transposition began in March 2017, along the east axis, which takes the waters of the São Franscisco River to the Paraíba do Norte River. Considering the difference in species composition (São Francisco, with 241 species and NMCE with 94, Barbosa et al 2017;Oliveira-Silva et al 2018, respectively) and its natural history, it is expected the occurrence of biological invasions between basins, a factor already observed in researches involving the transposition of basins (e.g., Ellender & Weyl, 2014;Shelton et al 2016), which could lead to the extinction of species in these ecosystems to the detriment of competition for space and resources (Pysek & Richardson, 2006). The current study aimed to provide an inventory of the ichthyofauna from Paraíba do Norte River basin prior to the transposition project.…”
Section: Introductionmentioning
confidence: 99%
“…The transposition began in March 2017, along the east axis, which takes the waters of the São Franscisco River to the Paraíba do Norte River. Considering the difference in species composition (São Francisco, with 241 species and NMCE with 94, Barbosa et al 2017;Oliveira-Silva et al 2018, respectively) and its natural history, it is expected the occurrence of biological invasions between basins, a factor already observed in researches involving the transposition of basins (e.g., Ellender & Weyl, 2014;Shelton et al 2016), which could lead to the extinction of species in these ecosystems to the detriment of competition for space and resources (Pysek & Richardson, 2006). The current study aimed to provide an inventory of the ichthyofauna from Paraíba do Norte River basin prior to the transposition project.…”
Section: Introductionmentioning
confidence: 99%
“…Headwater streams are critical habitats for conserving freshwater biodiversity (Clarke, Mac Nally, Bond, & Lake, ), but invasions by non‐native predatory fish can compromise the value of otherwise pristine headwater habitats as sanctuaries for native species within largely transformed riverscapes (Lepori, Benjamin, Fausch, & Baxter, ; Shelton, Clark, Sephaka, & Turpie, ). While both developed and developing countries recognize this threat, few of the latter have implemented control programmes to manage it (Pino‐Del‐Carpio, Miranda, & Puig, ).…”
Section: Introductionmentioning
confidence: 99%
“…The same applies to the Tsoelikane population which is differentiated from the other populations within the eastern lineage. Securing the survival of the Mohale lineage will be difficult due to the hydrological impact of the Mohale Dam and the introduction of alien Labeobarbus aeneus (Burchell, 1822) (Shelton et al, 2016). Until recently, this lineage contributed significantly to the overall genetic diversity of the species and was the largest population, but Shelton et al (2016) indicated that this population had crashed.…”
Section: Conservation Of Pseudobarbus Quathlambaementioning
confidence: 99%
“…Securing the survival of the Mohale lineage will be difficult due to the hydrological impact of the Mohale Dam and the introduction of alien Labeobarbus aeneus (Burchell, 1822) (Shelton et al, 2016). Until recently, this lineage contributed significantly to the overall genetic diversity of the species and was the largest population, but Shelton et al (2016) indicated that this population had crashed. Persistence of this lineage is now dependent on the survival of translocated populations in the Maletsunyane and Jordane rivers, and the conservation efforts being undertaken by Lesotho Highlands Developmental Authority (LHDA).…”
Section: Conservation Of Pseudobarbus Quathlambaementioning
confidence: 99%
See 1 more Smart Citation